2021
DOI: 10.18632/aging.203148
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of probable lipotoxic damage and myocardial fibrosis in epicardial obesity

Abstract: Myocardial fibrosis is considered a key pathological process in the development of cardiovascular diseases. In epicardial obesity (EO), the main cause of fibrosis development is lipotoxic myocardial damage. It is important to detect myocardial fibrosis at an early stage, using non-invasive diagnostic methods. According to the results of echocardiography (ECG), 110 men with general obesity were divided into the following two groups: Group I with epicardial fat thickness (tEAT) ≥ 7 mm (n = 70) and Group II with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…Moreover, EAT express higher levels of resistin, but lower levels of adiponectin and leptin [145][146][147]. It is well known that EAT thickness increases in obese subjects [148][149][150][151][152][153], and in these subjects, the levels of factors secreted by EAT, such as TNF-alpha, IL6, leptin, and free fatty acids, increase in comparison with non-obese subjects [154,155]. As for free fatty acids secreted by EAT in obese subjects, the metabolic signature of EAT is dominated by an increase of phosphatidylglycerol, phosphatidylcholine, and phosphatidylethanolamine [156].…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…Moreover, EAT express higher levels of resistin, but lower levels of adiponectin and leptin [145][146][147]. It is well known that EAT thickness increases in obese subjects [148][149][150][151][152][153], and in these subjects, the levels of factors secreted by EAT, such as TNF-alpha, IL6, leptin, and free fatty acids, increase in comparison with non-obese subjects [154,155]. As for free fatty acids secreted by EAT in obese subjects, the metabolic signature of EAT is dominated by an increase of phosphatidylglycerol, phosphatidylcholine, and phosphatidylethanolamine [156].…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…The present study found that EAT, especially LA-EAT, may contribute to cardiac structural and electrical remodeling and dysfunction, leading to the occurrence of AF. Previous studies showed that EAT can change the microenvironment and myocardial function around the LA by secreting pro-fibrosis and pro-inflammatory factors through direct contact with the LA myocardium, resulting in cardiac structural and electrical remodeling, such as myocardial fibrosis, slow conduction of electrical activities in the atrium and increased heterogeneity ( 17 , 18 ). Proliferative adipose tissue can extend into the myocardial cells along with the stroma, induce atrial fibrosis through fat infiltration, and changes the connection mode between myocardial cells, resulting in voltage reduction and abnormal conduction in the LA ( 19 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…1 Many studies have shown a certain relationship between EAT components and adverse cardiovascular events such as coronary artery stenosis, coronary atherosclerosis, myocardial ischemia, atrial fibrillation, coronary heart disease, myocardial fibrosis, and heart failure. [2][3][4][5][6][7][8] The EAT compositions will even play a leading role in coronary artery disease. 9 As the outbreak of COVID-19, some researchers have been working to explore the relationship between EAT components and the condition of COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…The EAT is mainly distributed between the atrioventricular groove and myocardial tissue inside the pericardium and extends along the coronary arteries 1 . Many studies have shown a certain relationship between EAT components and adverse cardiovascular events such as coronary artery stenosis, coronary atherosclerosis, myocardial ischemia, atrial fibrillation, coronary heart disease, myocardial fibrosis, and heart failure 2–8 . The EAT compositions will even play a leading role in coronary artery disease 9 .…”
Section: Introductionmentioning
confidence: 99%